Safety of Immunization for Children with Immune Thrombocytopenia - Xiangshi Wang; Tianxing Feng; Chuning Wang; Jingjing Li; Yanling Ge; Xiaowen Zhai; Hongsheng Wang; Mei Zeng (Vaccines, 2024)
Vaccine hesitancy is a common issue for children with immune thrombocytopenia (ITP) in China. The objective of this paper is to assess the immunization statuses of children with ITP, analyze the possible relationship between immunization and thrombocytopenia, and evaluate the safety of immunization after ITP remission. We included 186 children with an ITP history and followed up with them for two years after receiving re-immunization recommendations. The participants had an overall age-appropriate vaccine coverage of 57.9%. Vaccine-associated thrombocytopenia occurred in 99 (53.2%, 95% CI = 46.06–60.26) children ranging from 0 to 34 days following immunization, with 14 vaccines involved. One hundred and fifty-four (82.3%, 95% CI = 76.72–87.54) children were advised to restart immunization, whereas 32 (17.2%, 95% CI = 12.46–23.28) were advised to postpone partial or full vaccination. Following the follow-up, 150 (80.6%, 95% CI = 74.37–85.68) children completed the catch-up immunization, whereas 27 (14.5%, 95% CI = 10.17–20.30) partially completed it. Four patients with thrombocytopenia relapsed following the re-immunization. Incomplete catch-up immunization was related to the factors of chronic thrombocytopenia, vaccine-associated thrombocytopenia, and the relapse of ITP following re-immunization. ITP may occur after immunization with vaccines other than measles-containing vaccines. Re-immunization in children with ITP generally does not result in a relapse, regardless of whether the previous thrombocytopenia was vaccine-associated.